Gelsolin-like actin-capping protein has prognostic value and promotes tumorigenesis and epithelial-mesenchymal transition via the Hippo signaling pathway in human bladder cancer. (April 2019) - Zhaojie, Lyu; Yuchen, Liu; Miao, Chen; Yacun, Chen; Shayi, Wu; Anbang, He; Xinhui, Liao; Meng, Zhang; Peipei, Wu; Hongbing, Mei; Feng, Wang; Zhiming, Cai; et al.
Background: Transitional cell carcinoma (TCC) of the bladder, the major histologic subtype of bladder cancer, is increasing in incidence and mortality, which requires the identification of effective biomarkers. Actin-regulating proteins have recently been proposed as important antitumor druggable targets. As a gelsolin-family actin-modulating protein, CAPG (gelsolin-like actin-capping protein) generated great interest due to its crucial effects in various biological and physiological processes; however, the role and mechanism of CAPG in TCCs remain unknown. Materials and methods: Bioinformatic analysis and immunohistochemistry of clinical specimens were performed to detect the expression level of CAPG. Both in vitro and in vivo assays were used to determine the oncogenic effect of CAPG in TCCs. Male 4–5-week-old BALB/c nude mice were used for in vivo tumorigenesis assays, while SCID mice were used for in vivo metastatic assays. Affymetrix microarray was used to identify the underlying molecular mechanism. Western blot and immunofluorescence were used to validate the expression and localization of proteins. Results: CAPG was frequently upregulated in TCCs and associated with clinical aggressiveness and worse prognosis. Functional assays demonstrated that CAPG could contribute to the tumorigenesis, metastasis and epithelial-mesenchymal transition (EMT) of TCCs both in vitro and in vivo . A novel mechanism that CAPG promoted TCC development via inactivating the Hippo pathway, leading to a nucleus translocation of Yes-associated protein was suggested. Conclusions: The current study identified CAPG as a novel and critical oncogene in TCCs, supporting the pursuit of CAPG as a potential target for TCC intervention.